Question
upstudy study bank question image url

Ejercitación (1) Simplifica cada expresión. \( \begin{array}{ll}\text { a. } \sqrt[5]{-32}+(-1)^{\frac{2}{3}} & \text { b. } \frac{-4^{\frac{1}{2}}-\sqrt[5]{-243}}{\sqrt{121}} \\ \text { c. } \frac{\sqrt{100}-\sqrt[4]{16}}{\sqrt[18]{0}} & \text { d. }-64^{\frac{1}{3}} \cdot \sqrt{100}\end{array} \)

Ask by Vaughan Hampton. in Colombia
Mar 10,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

a. -1 b. 1/11 c. Indefinido d. -40

Solution

\( \textbf{a.} \) 1. Se tiene: \[ \sqrt[5]{-32} + (-1)^{\frac{2}{3}} \] 2. Notamos que \( -32 = -2^5 \), entonces: \[ \sqrt[5]{-32} = -2. \] 3. Para \( (-1)^{\frac{2}{3}} \) podemos escribir: \[ (-1)^{\frac{2}{3}} = \left((-1)^{\frac{1}{3}}\right)^2. \] 4. Como la raíz cúbica de \(-1\) es \(-1\), se tiene: \[ (-1)^{\frac{1}{3}} = -1 \quad \Rightarrow \quad \left((-1)^{\frac{1}{3}}\right)^2 = (-1)^2 = 1. \] 5. Sumando: \[ -2 + 1 = -1. \] --- \( \textbf{b.} \) 1. Se tiene: \[ \frac{-4^{\frac{1}{2}} - \sqrt[5]{-243}}{\sqrt{121}}. \] 2. En el término \( -4^{\frac{1}{2}} \) se entiende como el negativo de la raíz cuadrada de 4: \[ -4^{\frac{1}{2}} = -\sqrt{4} = -2. \] 3. Notamos que \( -243 = -3^5 \), luego: \[ \sqrt[5]{-243} = -3. \] 4. Sustituyendo en el numerador: \[ -2 - (-3) = -2 + 3 = 1. \] 5. El denominador es: \[ \sqrt{121} = 11. \] 6. Así, el resultado es: \[ \frac{1}{11}. \] --- \( \textbf{c.} \) 1. Se tiene: \[ \frac{\sqrt{100} - \sqrt[4]{16}}{\sqrt[18]{0}}. \] 2. Se calcula el numerador: \[ \sqrt{100} = 10 \quad \text{y} \quad \sqrt[4]{16} = 2. \] Entonces: \[ 10 - 2 = 8. \] 3. El denominador es: \[ \sqrt[18]{0} = 0^{\frac{1}{18}} = 0. \] 4. Al haber división por cero, la expresión es indefinida. --- \( \textbf{d.} \) 1. Se tiene: \[ -64^{\frac{1}{3}} \cdot \sqrt{100}. \] 2. Interpretamos \( -64^{\frac{1}{3}} \) como el negativo de la raíz cúbica de 64: \[ 64^{\frac{1}{3}} = 4, \quad \text{entonces} \quad -64^{\frac{1}{3}} = -4. \] 3. Además: \[ \sqrt{100} = 10. \] 4. El producto es: \[ -4 \cdot 10 = -40. \] --- Respuestas finales: \( \textbf{a.} \quad -1 \) \( \textbf{b.} \quad \frac{1}{11} \) \( \textbf{c.} \quad \text{Indefinido} \) \( \textbf{d.} \quad -40 \)

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

The Deep Dive

Para simplificar cada expresión, veamos cada caso: a. \(\sqrt[5]{-32} + (-1)^{\frac{2}{3}} = -2 + 1 = -1\) b. \(\frac{-4^{\frac{1}{2}} - \sqrt[5]{-243}}{\sqrt{121}} = \frac{-2 - (-3)}{11} = \frac{-2 + 3}{11} = \frac{1}{11}\) c. Esta expresión no se puede simplificar ya que \(\sqrt[18]{0}\) es indefinido. d. \(-64^{\frac{1}{3}} \cdot \sqrt{100} = -4 \cdot 10 = -40\)

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy